Longitudinal biomarker studies in human neuroimaging: capturing biological change of Alzheimer’s pathology - Fischer, Larissa; Parker, Dana; Maboudian, Samira; Fonseca, Corrina; Tato-Fernández, Claudia; Annen, Lucie; Arunachalam, Prithvi; Bacci, Julia R.; Barboure, Michelle; Capelli, Serena; Karagianni, Stamatia; Collij, Lyduine E.; et al. (BioMed Central, 2026)
Despite extensive research, open questions about the biological underpinnings of Alzheimer’s disease (AD) remain. Neuroimaging biomarkers based on positron emission tomography (PET) and magnetic resonance imaging (MRI) offer in vivo insights into these complex biological changes and interactions. However, most evidence to date comes from cross-sectional studies, limiting our understanding of disease progression. Longitudinal studies enable the investigation of biological changes within individuals, revealing how pathology evolves over time. With this review, we provide an overview of how longitudinal imaging biomarker studies have advanced the field and how they can contribute to future research. We highlight longitudinal biomarker studies that have provided critical insights into disease trajectories, staging, and individual variability. We further assess longitudinal multimodal studies which have elucidated interactions between AD-specific pathology, amyloid-β and tau, and broader biological changes like neurodegeneration, neuronal dysfunction, vascular disease, and inflammation. Further, we discuss associations of brain changes with symptomatology and clinical outcomes and conclude with challenges and future directions.